Anti-BEPS Measures and Their Impact on Business Performance of Multinational Enterprises - Svažič Tatjana (Naše gospodarstvo/Our economy, 2019)
This paper discusses the harmful tax practices of multinational enterprises (MNEs) and the fight of international organizations against them. We focus on the anti-tax base erosion and profit shifting project (anti-BEPS project) of the Organisation for Economic Co-operation and Development (OECD), namely its 15 actions, which we present in the first part of the paper, using descriptive and analytical methods. In the second part, we use critical and synthetic methods to assess how the selected aspects of multinational business will be impacted with described actions. Our conclusions show that MNEs will have to adapt their business structures and plans according to new tax regulations, which will also lower their profit levels due to unavailability of established harmful tax structures for lowering their tax bases. At the same time, our results indicate that the legal approach in introducing new measures on the subject field, lead to legal uncertainty in tax matters. Due to the scope of analysed problems, it was impossible to introduce individual problems in depth; however, we provide readers with the general characteristics and goals of introduced actions that are necessary for understanding our evaluation of their impact on certain fields of international business. Our paper contributes to literature and practice, as it provides general insight into recent and important international tax law developments that enterprises will have to consider when doing business across borders.